DEVELOPING ENVIRONMENT FRIENDLY GROWING MEDIA FOR SOILLESS CULTIVATION OF SEASONAL VEGETABLES - Sheeraz Aleem Brohi ,; Mahmood Laghari ,; Hafeez-ur-Rehman Mangio ,; Nizamuddin Depar , (Spectrum of Engineering Sciences, 2025)
The pursuit of sustainable agriculture, particularly in arid and semi-arid regions, necessitates alternatives to traditional soil-based cultivation. This study explores the development of environmentally friendly, cost-effective soilless growing media using locally available materials in Tandojam, Sindh, Pakistan. The objective was to identify optimal combinations of biomass, nutrient supplements, and stabilizers for cultivating seasonal vegetables, tomato (Solanum lycopersicum) and okra (Abelmoschus esculentus). Locally sourced materials were categorized into biomass ( coco peat, rice husk, wheat straw), supplements (e.g., compost, manure, biochar), and stabilizers (sands, expanded clay, styrofoam). These materials were dried, processed to 2-5 mm size, and mixed in volumetric ratios. Seventy-five media formulations were initially screened under greenhouse conditions. Based on germination rates (>70%) and seedling vigor, 15 treatments were selected for detailed analysis in a Randomized Complete Block Design (RCBD) with three replications. Comprehensive analysis of physico-chemical properties (WHC, porosity, pH, EC, nutrients) and plant growth parameters (germination, plant height, leaf and fruit number) was conducted. Results showed high WHC in banana leaves and coco peat (>82%), with high porosity in wheat straw and styrofoam. Media T32 (60% wheat straw, 20% biochar, 20% expanded clay) showed high vigor in both crops, while coco peat-based media T6 (50% coir, 25% compost, 25% pit sand) and T11 (60% coir, 20% compost, 20% pit sand) consistently achieved superior plant growth. However, bagasse and wheat straw-based media underperformed. Nutrient analysis revealed post-harvest depletion, highlighting the need for fertilization. This study concludes that coir-based media, combined with compost and structural stabilizers, offer a sustainable, low-cost solution for soilless vegetable cultivation in arid climates.